(untitled) (Pharmacy Practice, 2014)
Background: Previous studies of anti-hypertensive medicines utilization pattern in Nigeria showed that Angiotensin converting enzyme inhibitors (ACEIs) were often the least prescribed. However, the appropriate use of ACEIs in the black population achieves good blood pressure control and provides additional long term cardio- and renovascular protection benefits. Objective: To assess the current utilization pattern of anti-hypertensive medicines with specific emphasis on identifying possible shift in the frequency of use of ACEIs. Methods: A prospective cross-sectional assessment of the current utilization pattern of anti-hypertensive medicines was conducted among 300 randomly selected cohort at a 900-bed premier Teaching Hospital located in Ibadan, Southwestern Nigeria. The current utilization pattern was compared with the results of a study conducted at the same site and published 10 years ago. Results: Of the 300 random cohorts, a majority (79%) were females (237) with mean age 58.7 years (SD=2.81 years. Stage 2 hypertension was the most frequent diagnosis (54.3%). The utilization of ACEIs and long acting CCB (amlodipine) significantly increased from 8.6% and 21% (Ten years ago) to 29.93% and 36.68% respectively (p ˂ 0.0001). The use of thiazide diuretic and methyldopa declined significantly from 39.4% and 23.3% (Ten years ago) to 16.12% and 9.7% respectively (p ˂ 0.0001). Adverse drug reactions due to ACEIs were documented in 1.5% (3), while laboratory monitoring of serum potassium, urea and creatinine was conducted in only 37% (111) of cohort. Potentially harmful drug-drug interactions were identified in 25% (75) of cohorts, and the most frequent were ACEIs + NSAIDs (53.3%), ACEIs + amiloride / hydrochlorothiazide (22.6%). Conclusions: Anti-hypertensive medicines utilization has significantly shifted towards the increased use of ACEIs and long acting dihydropyridine CCBs. The use of thiazides and methyldopa has declined significantly. Physicians appeared more cognizant of the long term cardio- and renovascular benefits inherent in using ACEIs in a high cardiovascular risk group such as black hypertensive.